Development Of An Expert System For Assessment Of Reinforced Concrete Bridge Condition - Yardim, Yavuz (2002)
Condition assessment of Reinforced Concrete Bridge is a complex subject imbued with uncertainty and vagueness. This complexity arises from numbers and relations of problems in reinforced concrete bridges. Condition assessment process requires deep knowledge of the behavior of Reinforced Concrete Bridge, awareness of change, good understanding of design process and skillful person. This requirement can be achieved through a comprehensive expert system, which may represent human expertise. The aim of this project is to develop an expert system for condition assessment of reinforced concrete bridges. The system should be an efficient tool to guide the field inspectors during identification of potential problems associated with existing reinforced concrete bridges. It is developed by integrating the existing condition assessment procedures by the Public Work Department (JKR), which is only based on visual inspection, and the results obtained through non-destructive test (NDT) techniques and finite element analysis.The system has been successfully developed. Its final output, which not only is displayed on the monitor but also can be saved in a computer file and sent to a printer. Having this computation power, one file is created for each bridge at a particular area and quantitative comparison can be done faster and much more precisely than the available methods of condition assessment.